Mortality of motorcyclists in traffic accidents in the Brazilian Federal District from 1996 to 2007 - Montenegro, Marli de Mesquita Silva; Duarte, Elisabeth Carmen; Prado, Rogério Ruscitto do; Nascimento, Andréia de Fátima (Revista de Saúde Pública, 2011)
OBJECTIVE: To describe sociodemographic characteristics and analyze temporal trends in the mortality of motorcyclists injured in traffic accidents. METHODS: This was a time-series study with data from 580 motorcyclist deaths in the Brazilian Federal District from 1996 to 2007. The data were obtained from the Mortality Information System. Mortality rates specific for age and sex, the standardized rates (direct method), and the ratio of deaths per fleet (motorcycles) were calculated. The centralized moving average of the standardized mortality rate for men was calculated for a three-year period, and a linear regression model was constructed to study the evolution of mortality. The joinpoint method (inflection point) was used to calculate the annual increase in the standardized mortality rate. RESULTS: Most of the motorcyclists killed were male (94.3%), mixed skin color (71.0%), and between the ages of 20 and 39 years (73.8%). The standardized mortality rate for resident motorcyclists (men) was 1.9 to 7.2 deaths/100,000 men between 1996 and 2007. Between 1998 and 2007, the ratio of deaths per fleet increased from 2.0 deaths/10,000 motorcyclists to 10.0 deaths/10,000 motorcyclists among men. There was an estimated annual increase of 0.48 deaths/100,000 men (95%CI 0.31, 0.65; p